STRENGTHENING LOCAL WISDOM-BASED ENTREPRENEURSHIP AS AN EFFORT TO IMPROVE THE QUALITY OF EDUCATION IN SECONDARY SCHOOLS - Loso Judijanto; Rengga Yudha Santoso; Anif Istianah (Adisam Publisher, 2024)
The study aims to analyze how integrating local wisdom into the entrepreneurship curriculum can improve the quality of education in secondary schools. (SMK). Local wisdom-based entrepreneurship is seen as a means of connecting traditional values with modern market requirements, enabling students to acquire culturally and professionally relevant skills. The focus of this research is to identify ways in which local intelligence concepts can be integrated into entrepreneurial education and its impact on student skills development. This research takes a qualitative approach with literary research methods, analysing articles, books and documents related to the research context. The findings of this study suggest that local wisdom, when integrated into entrepreneurship learning in SMEs, can provide double benefits. First, it creates a competitive advantage for students by combining technical knowledge with a deep cultural understanding. Second, the emphasis on local intelligence in entrepreneurship facilitates the preservation of cultural heritage, helping students develop a work ethos that is rooted in their social values as well as their environment. Unfortunately, there are still obstacles, including resistance to curriculum changes and a lack of resources for teacher training. Nonetheless, evidence suggests that the success of this concept can improve the quality of education and better respond to local economic needs and the growth of new entrepreneurs.